Spontaneous generation of a biradical species of neocarzinostatin chromophore: role in DNA bulge-specific cleavage. - Hensens, O D (1994)
Detailed structure determination of the major and minor base-catalyzed degradation products of the chromophore of the enediyne anticancer antibiotic neocarzinostatin in the absence of DNA demonstrates that the enolate Michael addition reaction leading to a spirolactone cumulene intermediate is a spontaneous, stereoselective process. The implications of these findings for the mechanism of the thiol-independent, site-specific cleavage by the so-generated radical species of the drug at a DNA bulge are described.